Endothelin Receptor Antagonist Activity of (R)-(-)-2-(Benzo[l,3]dioxol-5-yl)-N-(4-isopropylphenylsulfonyl)-2- (6-methyl-2-propylpyridin-3-yloxy)acetamide Hydrochloride (PABSA) in Rat Aortic Smooth Muscle Cells and Isolated Rat Thoracic Aorta - Iwasaki, Takanori; Hayasaki-Kajiwara, Yoko; Matsuo, Yoshiyuki; Nakajima, Masatoshi (Arzneimittelforschung, 2001)
Antagonist activities of (R)-(-)-2-(benzo [l,3]dioxol-5-yl)-N-(4-isopropyl-phenylsulfonyl)-2-(6-methyl-2-propylpyridin-3-yloxy) acetamide-hydrochloride (CAS 188710-94-3, PABSA), a novel endothelin (ET) receptor antagonist, for ETA and ETB receptors were evaluated using rat aortic smooth muscle A7r5 cells and isolated rat thoracic aorta. PABSA concentration-dependently inhibited the ET-1-induced increase in intracellular calcium concentration ([Ca2+]i) mediated via ETA receptors in A7r5 cells with an IC50 of 0.17 nmol/l. PABSA antagonized the ETA receptor-mediated contraction induced by ET-1 in endothelium-denuded rat aorta with a Kb of 0.74 nmol/l. The potency of PABSA in inhibiting ETA receptor-mediated vaso-contraction was approximately 40- and 100-fold greater than those of BQ-123, a selective ETA antagonist, and bosentan, a mixed ETA/ETB receptor antagonist, respectively. ETB receptor-mediated endothelium-dependent vasorelaxation induced by ET-3 in the aorta was also antagonized by PABSA, with a Kb of 9.8 nmol/l. In contrast, PABSA affected neither the vasocontraction induced by KCl or norepinephrine nor the vasorelaxation induced by acetylcholine or prostaglandin I2 in the aorta. These results suggest that PABSA is a highly potent and selective ETA receptor antagonist.
Keywords: (R)-(-)-2-(Benzo[l,3]dioxol-5-yl)-N-(4-isopropylphenylsulfo-nyl)-2-(6-methyl-2-propylpy; -ridin-3-yloxy) acetamide hydrochloride; CAS 188710-94-3; Endothelin receptor antagonist; PABSA, endothelin receptor antagonist activity, rat aorta